Gender and Professional Ethics in the IT Industry - Panteli, Androniki (Journal of business ethics, 1999)
In this paper, we discuss the ethical responsibility of the Information Technology (IT) industry towards its female workforce. Although the growing IT industry experiences skills shortages, there is a declining trend in the representation of women. The paper presents evidence that the IT industry is not gender-neutral and that it does little to promote or retain its female workforce. We urge that professional codes of ethics in IT should be revised to take into account the diverse needs of its staff.